THE EFFECT OF SURFACTANTS ON THE CHEMILUMINESCENT REACTION OF LUMINOL WITH HYDROGEN PEROXIDE - D. A. Ibragimova; O. M. Kamil; T. V. Yankova; N. A. Yashtulov; N. K. Zaitsev (Тонкие химические технологии)
The luminol-hydrogen peroxide chemiluminescent system is widely used for the creation of diagnostic systems, for chemical analysis, for studying the kinetics and mechanisms of chemical reactions, for the creation of special and emergency light sources, and for monitoring living systems. However, the use of the luminol-hydrogen peroxide chemiluminescent system is limited by the fact that there are almost no ways of managing the reaction. The introduction of organized molecular systems into the luminol-hydrogen peroxide chemiluminescent system can create an additional channel for controlling chemiluminescent reactions. The luminol-hydrogen peroxide system was not previously studied in various classes of hydrocarbon and perfluorinated micellar solutions. This work was the first to study the effect of cationic, anionic and nonionic hydrocarbon surface-active substances (cetyltrimethylammonium bromide, sodium decyl sulfate, sodium dodecyl sulfate, triton X 100) and perfluorinated surface-active substances (FT-135 and FT-248) on the chemiluminescent systems luminol-hydrogen peroxide-potassium hexacyanoferrate(III) and luminol-hydrogen peroxide-copper(II) sulphate. The systems retain the ability to chemiluminescence in the presence of a surfactant. Cationic surfactants lower the intensity of chemiluminescence, and anionic surfactants increase the intensity of chemiluminescence. The introduction of a surfactant into the system allows increasing the range of dependence of the chemiluminescence intensity on the catalyst concentration. Kinetic curves of the growth and decay of chemiluminescence were measured in the systems. The rate constants of the chemiluminescence decay were measured in the framework of the first-order kinetics model.